Higher taxes on less elastic goods? Evidence from German municipalities - Sebastian Blesse; Philipp Doerrenberg; Anna Rauch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
German municipalities have substantial autonomy in setting taxes on two distinct tax bases: business profits and property values. We use this setting and a two-step approach to explore whether implemented tax policy is consistent with the seminal inverse-elasticity rule. First, we estimate the tax elasticity of the two tax bases using event-study and generalized differences-in-differences methods based on the universe of municipalities in 1995-2010. Second, we compare the ratio of the observed tax rates for the two tax bases to the ratio of their estimated elasticities. We find that property is not very responsive to variation in tax rates, whereas business profits respond significantly. While this would suggest that property should be taxed at a higher rate, the data show that this not the case: most municipalities impose relatively higher rates on business profits. This suggests that municipality-level taxation in Germany is inconsistent with the inverse-elasticity rule. We provide suggestive evidence that this finding is explained by politician's imprecise expectations about revenue elasticities as well as re-election concerns.
Keywords: H2; H3; H7; R5; 330; Inverse-elasticity rule; Property taxes; Business taxes; Municipality-level taxation; Elasticity of Corporate Taxable Income